Sesame milk yoghurt with the addition of red dragon fruit extract - Suhartatik, Nanik; Widanti, Yannie Asrie; Anwar, Sokhif Saiful (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 5 No 1 (2018): Scientific Journal of Food Technology, 2018)
Some research on yogurt from sesame milk has been done. The process of fermentation is intended to reduce the aroma and flavor of sesame milk that is less favored by consumers and improve its functional properties. This study aimed to study the ability of red dragon fruit extract on yogurt of sesame milk. The research was conducted by using Factorial Completely Random Design with the first factor was the ratio of sesame seed to water (10, 12, and 14%) and second factor addition of red dragon fruit extract (2, 5, and 8%). Parameter analyzes include sugar levels, protein levels, pH, and total titrated acids. Data were analyzed by two way ANOVA to express the real difference between treatments. The results showed that the variation in the proportion of sesame seeds and red dragon extract did not significantly influence the sugar content, protein content, pH, and the acidity level of the sesame milk yoghurt. yoghurt from sesame milk-red dragon fruit extract gives sugar content ranging from 1.00-5.25 g/100 ml; dissolved protein 19,83-26,89 g/100 ml; pH 4,90-5,43; and titratable acid 1,25-1,76. The lowest pH for sesame milk yoghurt was yoghurt with 10% of sesame and 2% of dragon fruit.